Eye of a needle - Fick, Cornelia (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2016)
Most of my stories are about interpersonal relationships between the sexes, as well as intrapersonal processes, such as growing old. I have a deep connection to such themes because of my background as a general nurse and midwife; meeting too many abused women in hospitals, and the broader community. Because patterns of abuse tend to become invisible, I use experimental forms of storytelling as well as sharp, ironic and dark humour as a way to make this side of life more visible. My reading has shown me how experimental forms can render seemingly timeless or ageless topics in a fresh, vital way.
Keywords: Uncatalogued